Composite tooling design - Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2008)
This program explores the wide variety of materials used to create composite tooling, including: glass reinforced polyester/vinyl-ester laminated tooling; carbon/glass fiber reinforced epoxy/bismaleimide laminated tooling; invar; invar coated carbon fiber reinforced tooling; steel
Title from title screen
DVD format
Keywords: Tools -- Design and construction; Machine-shop practice; Human engineering